Implementation Practice of Social and Cultural Values in Rural Development - Hadiprashada, Dhanurseto (2016)
The problems that always arise in a variety of conditions and levels of lead quality development in the area to be blocked. National development trying to adopt the modernizing approach made the clash of class in Indonesia is increasingly becoming. The implementation of national development policies to create a good governance realized by various policies. Along with increasing the quality of human resources, and open access to information in the community needed proper communication patterns in the implementation of regional development policy. Through the Undang-Undang Desa No. 6 Tahun 2014 Pasal 67 which states that the village has the right to regulate and manage the interests of society based on rights origin, customs and socio-cultural values of rural communities, of course, can cause problems of its own in the community. One is the management of natural resources and the environment. This paper aims to describe the practice of communication such as what is applied in sustainable development in the region. It means that the socio-cultural values of the community can match the pattern of regional development. Object of study in this paper is in the village of Ulak Bandung, Muara sahung, Kaur District, Bengkulu Province.